2016
DOI: 10.1016/j.advwatres.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Scour patterns around isolated vegetation elements

Abstract: 10The complex multi-directional interactions between hydrological, biological and fluvial processes govern the formation and evolution of river landscapes. In this context, as key geomorphological agents, riparian trees are particularly important in trapping sediment and constructing distinct landforms, which subsequently evolve to larger ones. The primary objective of this paper is to experimentally investigate the scour/deposition patterns around different forms of individual vegetation elements. Flume exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…A series of visualization experiments conducted by Valyrakis et al [6], confirm that turbulence and large-scale vortices were generated at a certain distance after the vegetation elements. Similar studies have shown that a direct link exists between the size of eddies shed downstream from vegetation elements and their capacity to scour the bed surface [7].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A series of visualization experiments conducted by Valyrakis et al [6], confirm that turbulence and large-scale vortices were generated at a certain distance after the vegetation elements. Similar studies have shown that a direct link exists between the size of eddies shed downstream from vegetation elements and their capacity to scour the bed surface [7].…”
Section: Introductionmentioning
confidence: 79%
“…Even though bed-shear stresses have been used as the standard criterion for assessing riverbed and riverbank erosion, recent criteria put strong emphasis on the role of flow turbulence and coherent flow structures [7,24,25]. Likewise, contemporary research on riparian vegetation hydrodynamics and their potential implications for sediment transport suggest that there is little certainty that shear stresses are the sole criterion to accurately describe these interactions and propose criteria based on turbulent fluctuations [37].…”
Section: Turbulence Intensitymentioning
confidence: 99%
“…We were surprised to find that biomass and width did not affect bedform height -this could be a function of too short a test duration. Localized vegetation scour (erosion around the plant, especially at its upwind face) has been observed to increase as porosity decreases in emergent and submerged vegetation (Yagci et al 2016) such that we would have expected less accretion with greater biomass and stem width. We believe the erosion or scour we observed in the high-density boxes is a function of overlapping wake zones in the sheltered lee side of plants and interaction among leaves when plants are spaced closer together.…”
Section: Discussionmentioning
confidence: 90%
“…However, solid vs. porous vegetated obstructions do not respond equivalently with regards to flow field and sediment flux responses (Gillies et al 2014), and therefore, we would not expect plants to either. Similarly, artificial cylinder-like obstructions have been found to produce more volumetric deposition than actual porous plants, so tests on artificial obstructions may not translate to conditions observed in nature (Yagci et al 2016). Being flexible, plants will undergo streamlining and compression and thus yield more variable heterogeneous velocity field results compared to solid objects.…”
Section: Discussionmentioning
confidence: 99%
“…Water-quality issues, changes in the wet cross-section, increased flooding risk and obstruction of navigation, as a result of excessive depositions, effects on the aquatic ecosystems, decline of macrophyte growth, clogging of spawning gravel, pressures inflicted on coastal zones, effective diminution of dams' storage volume, due to excessive sedimentation, and extreme erosion rates in the case of sediment-starved water (usually below storage dams-theory of hungry water) [6][7][8][9][10][11], are some of the effects of sediments, which constitute the driving force behind the investigation of sediment transport processes, as well as modeling and quantification efforts. Moreover, knowledge about the interrelated interactions among water-biota-sediment in natural rivers is one of the central issues in today's sustainable river management [12].…”
Section: Introductionmentioning
confidence: 99%